Non-communicable disease (NCD) corners in public sector health facilities in Bangladesh: a qualitative study assessing challenges and opportunities for improving NCD services at the primary healthcare level - Syed Masud Ahmed; Tuhin Biswas; Sheikh Mohammed Shariful Islam; Lal B Rawal; Kie Kanda; Md. Imtiaz Tanim; Prakash Poudel; Andre M N Renzaho; Abu S Abdullah (BMJ Open, 2019)
Objective To explore healthcare providers’ perspective on non-communicable disease (NCD) prevention and management services provided through the NCD corners in Bangladesh and to examine challenges and opportunities for strengthening NCD services delivery at the primary healthcare level.Design We used a grounded theory approach involving in-depth qualitative interviews with healthcare providers. We also used a health facility observation checklist to assess the NCD corners’ service readiness. Furthermore, a stakeholder meeting with participants from the government, non-government organisations (NGOs), private sector, universities and news media was conducted.Setting Twelve subdistrict health facilities, locally known as upazila health complex (UHC), across four administrative divisions.Participants Participants for the in-depth qualitative interviews were health service providers, namely upazila health and family planning officers (n=4), resident medical officers (n=6), medical doctors (n=4) and civil surgeons (n=1). Participants for the stakeholder meeting were health policy makers, health programme managers, researchers, academicians, NGO workers, private health practitioners and news media reporters.Results Participants reported that diabetes, hypertension and chronic obstructive pulmonary disease were the major NCD-related problems. All participants acknowledged the governments’ initiative to establish the NCD corners to support NCD service delivery. Participants thought the NCD corners have contributed substantially to increase NCD awareness, deliver NCD care and provide referral services. However, participants identified challenges including lack of specific guidelines and standard operating procedures; lack of trained human resources; inadequate laboratory facilities, logistics and medications; and poor recording and reporting systems.Conclusion The initiative taken by the Government of Bangladesh to set up the NCD corners at the primary healthcare level is appreciative. However, the NCD corners are still at nascent stage to provide prevention and management services for common NCDs. These findings need to be taken into consideration while expanding the NCD corners in other UHCs throughout the country.